The puberty ritual in Sri Lanka: a comparative exploration of perceptions and attitudes between Buddhists and Christians - Kim, Paul Mantae (American university studies / 7, 2011)
Theoretical perspective -- Methodology -- Understanding the context of the Sinhalese puberty ritual -- The Sinhalese Buddhist perception of the puberty ritual -- Comparison of the attitudes between Sinhalese Buddhists and Sinhalese Christians -- Approaching the Sinhalese puberty ritual in light of the Bible -- Contextualization and its implications for the Christian practice of puberty -- The Sinhalese Christian appraisal of the puberty ritual -- Concluding implications : missiological insights regarding the Sinhalese puberty ritual